Realism And Islamic Education - Ine Ratu Fadliah (Edumaspul: Jurnal Pendidikan, 2022)
This study describes realism and Islamic education. The method used in this study uses the library research, that literature or literature study can be interpreted as a series of activities related to library data collection methods, reading and recording and processing research materials. The results of this study indicate that education can be interpreted narrowly, and can also be interpreted broadly. Narrowly education can be interpreted: "guidance given to children until they are adults. While education in a broad sense is everything related to the process of human development and development, namely efforts to develop and instill values ​​for students, so that the values ​​contained in education become part of the child's personality which in turn he becomes a smart person, both , capable of living and useful to society.